The interplay of user preference and precision in different gaze-based interaction methods in virtual environments - Severitt, Björn R.; Sauer, Yannick; Neugebauer, Alexander; Agarwala, Rajat; Castner, Nora; Wahl, Siegfried (Frontiers in Virtual Reality, 2025)
IntroductionExtended reality (XR) technologies, particularly gaze‐based interaction methods, have evolved significantly in recent years to improve accessibility and reach broader user communities. While previous research has improved the simplicity and inclusivity of gaze-based choice, the adaptability of such systems ‐ particularly in terms of user comfort and fault tolerance ‐ has not yet been fully explored.MethodsIn this study, four gaze‐based interaction techniques were examined in a visual search game in virtual reality (VR). A total of 52 participants were involved. The techniques tested included selection by dwell time, confirmation by head orientation, nodding and smooth pursuit eye movements. Both subjective and objective performance measures were assessed, using the NASA‐TLX for perceived task load and time to complete the task and score for objective evaluation.ResultsSignificant differences were found between the interaction techniques in terms of NASA‐TLX dimensions, target search time and overall performance. The results indicate different levels of efficiency and intuitiveness of each method. Gender differences in interaction preferences and cognitive load were also found.DiscussionThese findings highlight the importance of personalizing gaze‐based VR interfaces to the individual user to improve accessibility, reduce cognitive load and enhance the user experience. Personalizing gaze interaction strategies can support more inclusive and effective VR systems that benefit both general and accessibility‐focused populations.